PEMANFAATAN BEBERAPA JENIS DAN DOSIS LIMBAH KELAPA SAWIT (Elaeis guinensis Jacq) TERHADAP PERUBAHAN PH, N, P, K TANAH PODSOLIK MERAH KUNING (PMK) - FITRI RAMADHANI; ERVINA ARYANTI; ROBBANA SARAGIH (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
This research has been conducted on January until February 2015 at Agrostologi laboratory, industrial feed and soil science laboratory, in State Islamic University Sultan Syarif Kasim Riau. The purposed of the research was to determine the effect of bunch ash, boiler ash, and palm oil sludge with different doses of the red-yellow podsolic fertility. The research used random sampling method that consist of (1). Red-yellow podzolic soil with a bunch ash as much as 5 ton/ha (25 g), 10 ton/ha (50 g), 15 ton/ha (75 g). (2). Red-yellow podzolic soil with boiler ash as much as 5 ton/ha (25 g), 10 ton/ha (75 g), 15 ton/ha (75 g). (3). Red-yellow podzolic soil with sludge as much as 5 ton/ha (25 g), 10 ton/ha (50 g), 15 ton/ha (75 g). Total of treatment were 20 pollybag. Parameters observation consist of value pH H2O, N, P, K. The results showed that bunch ash doses of 15 ton/ha was the best material to improvement of soil chemical properties red-yellow podzolic (pH H2O, P and K), subsequently followed by boiler ash, but a decline N of giving bunch ash and boiler ash while sludge doses 15 ton/ha is the best material to improvement of soil chemical properties N.